2019
DOI: 10.3762/bjoc.15.248
|View full text |Cite
|
Sign up to set email alerts
|

Probing of local polarity in poly(methyl methacrylate) with the charge transfer transition in Nile red

Abstract: The permittivity of polymers and its spatial distribution play a crucial role in the behavior of thin films, such as those used, e.g., as sensor coatings. In an attempt to develop a conclusive approach to determine these quantities, the polarity of the model polymer poly(methyl methacrylate) (PMMA) in 600 nm thin films on a glass support was probed by the energy of the charge transfer transition in the oxazine dye Nile red (NR) at 25 °C. The absorption and fluorescence spectra of NR were observed to shift to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…In future, complementary conceptual methods as the Kawski model [76] should be also used in comparison to the conception of this work. The analysis of solvatochromic effects of appropriate solvatochromic probe molecules such as Nile red is recommended [77–81] . It is suggested that this probe may be useful to better understand the different relationships f( n ) as a function of N for the different solvent classes, because the solvatochromic property of Nile red is strongly determined by the solvent class [79,81] …”
Section: Discussionmentioning
confidence: 99%
“…In future, complementary conceptual methods as the Kawski model [76] should be also used in comparison to the conception of this work. The analysis of solvatochromic effects of appropriate solvatochromic probe molecules such as Nile red is recommended [77–81] . It is suggested that this probe may be useful to better understand the different relationships f( n ) as a function of N for the different solvent classes, because the solvatochromic property of Nile red is strongly determined by the solvent class [79,81] …”
Section: Discussionmentioning
confidence: 99%
“…The first observation can be attributed to a much lower Δµ in the case of NR (established at ca. 6.30 D) [7], which leads to a less pronounced bathochromic shift in emission (ca. 3000 cm −1 against ca.…”
Section: Resultsmentioning
confidence: 99%
“…Steady-state emission spectroscopy also allows probing local permittivity in polymers and has been used to characterize spatial heterogeneity of ε in polymeric films through single molecule or fluorescence microscopy studies [3,5]. Nile Red (NR) has been widely used as a luminescent dye in these approaches, owing to its photostability and convenient optical properties including high photoluminescence quantum yield (PLQY) and absorption and emission spectra strongly sensitive to the local environment [7,8]. NR has also been particularly used in biological applications, for instance in the detection of proteins from the spectral position of its fluorescence, or to determine intracellular local polarity from the variation of its lifetime (τ F ) in fluorescence lifetime imaging spectroscopy (FLIM) [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations